Development Idiosyncratic Deals and Employee Performance - Tauba, Mariam; Kimwolo, Andrew (SEISENSE Journal of Management, 2021)
Employee performance has been at the helm of academic research over the years. The changing nature of work has unearthed several antecedents of job performance. The purpose of this study was to examine employee performance through the development of Idiosyncratic deals and Leader-Member-Exchange-quality lens of antecedents. The study is anchored on the social exchange theory. The hypotheses were tested on a sample of 325 employees of ICT firms in Uganda, using a cross-sectional survey. Three hundred two responses were used for analysis after cleaning of data. The direct hypotheses were tested using correlation analysis, while the mediation was tested using the Hayes Process macro model 4. The results supported the relationship between development idiosyncratic deals and employee performance and LMX quality and employee performance. This study found a significant mediating role of LMX-quality on the relationship between development idiosyncratic deals and employee performance. The study made contributions to the literature on idiosyncratic deals, employee performance, leader-member exchange quality as well, as the Social exchange theory. The study recommends adopting good quality LMX relationships to enhance the role of development idiosyncratic deals on employee performance among ICT firms.